Prevalence of Mitral Valve Prolapse Among Individuals with Pectus Excavatum: A Systematic Review and Meta-Analysis - Andrea Sonaglioni; Antonino Bruno; Alessio Polymeropoulos; Gian Luigi Nicolosi; Michele Lombardo; Paola Muti (Diagnostics)
Background: During the last decades, a small number of studies reported a wide range of variability in the estimated prevalence of mitral valve prolapse (MVP) among individuals with pectus excavatum (PE). The present systematic review and meta-analysis has been primarily designed to summarize the main findings of these studies and to estimate the overall prevalence of MVP among PE individuals. Methods: All imaging studies assessing the prevalence of MVP in PE individuals vs. healthy controls, selected from PubMed and EMBASE databases, were included. The risk of bias was assessed by using the National Institutes of Health (NIH) Quality Assessment of Case–Control Studies. Events (presence of MVP) and nonevents (absence of MVP) in PE individuals and control groups were recorded. The main outcome was the measure of odds ratio (OR) for MVP presence pooled with 95% confidence intervals, using a fixed-effects model. Results: The full texts of eight studies with 303 PE patients (mean age 25.7 yrs) and 498 healthy controls (mean age 31 yrs) were analyzed. Three studies assessed MVP prevalence in children and early adolescents, whereas the remaining five studies examined PE adults. The prevalence of MVP in PE individuals and healthy controls was 40.6% and 12.8%, respectively. In the pooled sample, the OR for MVP presence was significantly higher in PE individuals compared to controls (OR = 5.80, 95%CI = 3.83–8.78, Z = 8.30, p < 0.001). Subgroup analysis revealed that MVP prevalence was approximately three-fold higher among PE children and early adolescents compared with PE adults. Overall, high consistency was observed in the pooled effect sizes, due to the low statistical heterogeneity among the included studies (I2 = 22.7%, p = 0.25). Egger’s test for a regression intercept gave a p-value of 0.07, indicating no publication bias. The sensitivity analysis supported the robustness of the results. Conclusions: PE individuals are nearly six times more likely to have MVP than controls. MVP prevalence is three-fold higher in PE individuals during childhood and early adolescence, compared to PE adults. Given the strong association between MVP and PE, MVP should be suspected in all individuals with anterior chest wall deformity.